Student and teacher perceptions of teaching/learning processes in classrooms: how close is the partnership? - Barker, Robert G.; Moroz, Wally (The Australian journal of teacher education, 1997)
This paper investigates the differing perceptions of the teaching / learning partnership in the classrooms and explores ways to bridge this perceptual gap and improve the status of an important core subject, viz social studies, in our schools. The paper suggests that an interactive and collaborative partnership between teachers and students in the classroom will elicit a more positive learning environment.